2019
DOI: 10.1016/j.bbr.2018.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Differential fear conditioning generates prefrontal neural ensembles of safety signals

Abstract: Fear discrimination is critical for survival, while fear generalization is effective for avoiding dangerous situations. Overgeneralized fear is a typical symptom of anxiety disorders, including generalized anxiety disorder and posttraumatic stress disorder (PTSD). Previous research demonstrated that fear discrimination learning is mediated by prefrontal mechanisms. While the prelimbic (PL) and infralimbic (IL) subdivisions of the medial prefrontal cortex (mPFC) are recognized for their excitatory and inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 76 publications
5
30
0
Order By: Relevance
“…Our finding of fear discrimination in males accompanied by differences in oscillatory activity in mPFC during CS+ vs CS− presentation at retrieval adds to growing evidence of the involvement of this region in fear discrimination [27][28][29][30][31][32][33][34][35][36] . Although we found quantitative differences in theta and gamma power between CS+ and CS− presentation when activity was averaged over the entire frequency band and cue duration (see below), no qualitative differences were apparent when activity was examined throughout each frequency band or cue www.nature.com/scientificreports www.nature.com/scientificreports/ duration.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our finding of fear discrimination in males accompanied by differences in oscillatory activity in mPFC during CS+ vs CS− presentation at retrieval adds to growing evidence of the involvement of this region in fear discrimination [27][28][29][30][31][32][33][34][35][36] . Although we found quantitative differences in theta and gamma power between CS+ and CS− presentation when activity was averaged over the entire frequency band and cue duration (see below), no qualitative differences were apparent when activity was examined throughout each frequency band or cue www.nature.com/scientificreports www.nature.com/scientificreports/ duration.…”
Section: Discussionsupporting
confidence: 71%
“…In this study we determined if sex differences in auditory fear discrimination involve altered mPFC function. As with fear extinction, mPFC plays a key role in fear discrimination [27][28][29][30][31][32][33] . Moreover, theta and gamma oscillations in mPFC are also implicated in fear discrimination 34,35 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fear conditioning has been widely used as a model for PTSD in rodent studies (Rasmusson and Charney, 1997;Morrison and Ressler, 2014;Bali and Jaggi, 2015), and fear memories are encoded as engrams across multiple brain regions (Josselyn et al, 2015) and Grella et al,16 activation of these engrams has been shown to be both necessary and sufficient to drive fear responses. However, while the foundation for cortical traces are laid down early during encoding (Lesburgueres et al, 2011;Wang et al, 2012;Cardenas et al, 2019;Corches et al, 2019;Jacques et al, 2019) there is evidence to suggest that the PFC neurons involved in fear memory retrieval are not the same neurons active during encoding (Giannotti et al, 2019;DeNardo et al, 2019). Within the PFC, we specifically looked at the PL for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In rodent studies, the PL has been implicated in the expression and renewal of fear responses (Corcoran and Quirk, 2007;Sierra-Mercado et al, 2011;Orsini and Maren, 2012;Courtin et al, 2014;Fenton et al, 2014;Corches et al, 2019) and increased activity in this region is associated with extinction deficits (Burgos-Robles et al, 2009) as well as increased input to the basolateral amygdala (BLA) (Likhtik et al, 2005;Maren et al, 2013), an output which promotes freezing behavior and fear (Vidal- Gonzalez et al, 2006).…”
Section: Discussionmentioning
confidence: 99%